Spectral and Biological Studies of Dioxouranium(VI), Dioxomolybdenum(VI), Oxovanadium(II) Complexes of o-Hydroxy Acetophenone Oxime - Mehta, B.H.; Syed, F.F. (Asian Journal of Chemistry, 2010)
The ketone o-hydroxyacetophenone was treated with hydroxylamine hydrochloride for the synthesis of its oxime derivative. The oxime was used to synthesize dioxouranium(VI), dioxomolybdenum(VI) and oxovanadium(II) complexes having metal : ligand and the metal complexes were characterised by elemental analyses, molar conductivity measurements, magnetic susceptibility measurements, ESR spectral data, electronic absorption. IR absorption spectral data and 1H NMR spectral data. Dioxouranium and dioxomolybdenum complexes were found to be diamagnetic, whereas oxovanadium complex was found to be paramagnetic in nature. The ligand and the metal complexes were also studied for their antibacterial activity. On the basis of the investigation appropriate geometry was assigned to the metal complexes.